Spatial variation of Melaleuca cajuputi powell essential oils - Hafizan, Juahir; Adiana, Ghazali; Fathurrahman, Lananan
Cajuputi essential oil in Indonesia and Malaysia is extracted from the leaves of Melaleuca cajuputi Powell. This study identify the variation of Melaleuca cajuputi essential oil fingerprinting based on the essential oil. The leaves were collected from 10 different sites in Terengganu undergoes hydro distillation and detailed analysis by FTIR spectroscopy. ATR-FTIR result of Melaleuca cajuputi shows that functional group of Gelam are variable between different sites and also gave different fingerprinting characters due to the compound variation in relation to their adaptation to the changing environment. Result shows high correlation between several sites (0.97, 0.98 and 0.976) and also significant difference between different sampling stations (p-value < 0.01). The present study proved a significant spatial variation of Melaleuca cajuputi fingerprint in Terengganu from the essential oil collected.